Prevalence of Frailty and Related Factors Among Community-Dwelling Older Adults: A Cross-Sectional Study from Western Türkiye. - PALA, Fahriye; YALÇIN GÜRSOY, Melike (Turkiye Klinikleri Journal of Nursing Sciences, 2023)
Objective: This study aimed to determine the prevalence of frailty and related factors among community-dwelling older adults. Material and Methods: This cross-sectional study included 400 older people aged ≥65 years living in a city center in western Türkiye. The FRAIL Scale was used to evaluate frailty, the Mini Nutritional Assessment-Short Form (MNA-SF) was used to assess nutritional status, and the Katz Activities of Daily Living (Katz ADL) Scale was used to evaluate daily life activities. Multivariate analysis was performed using SPSS software. Results: Of the elderly participants, 24.5% were frail, and 44.2% were pre-frail. Additionally, frailty was observed 4.3 times in those aged ≥75 years, 3.1 times in those who used 5 or more drugs, 5.7 times in those with a medium perception of health, 30.6 times in those with poor/very poor health perception, and 2.2 times in those with a history of falling in the previous year. Conclusion: The results of this study show that approximately one in every four older people is frail, one in every two older people is pre-frail, and various variables are associated with frailty. It may be recommended that the older adults be screened regularly for frailty by nurses in primary health care institutions.